The relationship between working posture and complaints of Musculoskeletal Disorders (MSDS) in PT Workers. Pertamina Patra Niaga Fuel Terminal Sibolga - Malau, Nurlyani; Ashar, Yulia Khairina; Ismah, Zata (Science Midwifery, 2024)
This aim of this research is to determine the relationship between work posture and complaints of Musculoskeletal Disorders in PT workers. Pertamina Patra Niaga Fuel Terminal Sibolga This research is an observational study, with a cross sectional approach, the research was conducted on March 25-April 18 2023. The population at this research site was 40 workers with a sample size of 35 people. The sampling technique was carried out by total sampling. The analysis used is univariate and bivariate, using statistical test data processing using Chi-Square. The research results show that PT. Pertamina Patra Niaga Fuel Terminal Sibolga 15 people (42.9%) have a work posture with a high risk level, 20 people (57.1%) have a medium risk level. Meanwhile, the results of the level of Musculoskeletal Disorders complaints among PT workers. Pertamina Patra Niaga Fuel Terminal Sibolga for the medium category was 26 people (74.3%), and for the light category there were 9 people (25.7%). The results of the Chi-Square statistical test obtained a p value of 0.048 ≤ (0.05), which means there is a relationship between work posture and MSDs complaints among PT workers. Pertamina Patra Niaga Fuel Terminal Sibolga 2023. To reduce the risk of work posture which can cause MSDs complaints, workers are advised to do stretching movements before carrying out work activities.